Women Empowerment: An Analysis of Influence on Gender Equality in Eban Village, Timor Tengah Utara - Marisa Susanty Bette Seran; Surya Yudha Regif; Andre Pattipeilohy (East Asian Journal of Multidisciplinary Research, 2023)
This study analyzes the Influence of Women Empowerment on Gender Equality. The sample in this study was 128 women in Eban Village, Timor Tengah Utara Regency. The results showed that the variable Women Empowerment in Women in Eban Village, North Central Timor Regency had a significant effect on Gender Equality by 0.513. The presentation of the data can be seen that the Women Empowerment (X) variable has a positive regression coefficient value of 0.707. The value of this positive regression coefficient shows that if there is an increase of one percent in the Women Empowerment (X) variable, it will increase the value of Gender Equality by 70.7%. Indigenous women in Eban Village are the successors of identity for the sustainability of dawan traditional culture through weaver groups which can be passed on to the next generation. This potential becomes social and economic capital for the development of cultural identity through the involvement and participation of women in Eban Village.